Percepcja produktu w kontekście przekazu reklamowego – analiza na podstawie dwu metod badania podobieństwa - Banaszczyk, Małgorzata (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
The purpose of the study was to show that interpretation of observed objects depends on the context (in this case context was the advertisement) in which they are seen. The second goal was to show the equivalence of two methods used to investigate similarity between objects – affinity index and comparison in pairs. The group of 180 people aged 19–32 participated in the study. They valuated similarity between three identical objects but advertised in three different ways. Using multidimensional scaling method the perception maps of the three products were created. Data unequivocally proved that they were seen as dissimilar. The Pindis procedure revealed that both methods used to investigate similarity are methodologically equivalent. They can be used interchangeably.